Sewall family papers - Sewall, Thomas
Letter from Rebecca Webster to the Rev. Thomas Sewall regarding his father, Dr. Thomas Sewall (1786 or 7-1845) and two reminiscences by Margaret Cruickshank relating to Dr. Sewall's household in Washington, D.C.
Typewritten transcripts.
Clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Sewall, Thomas, -- 1786 or 1787-1845.; Cruickshank, Margaret; Webster, Rebecca -- Correspondence; Sewell family; Washington (D.C.) -- Social life and customs; Clergy